S-10-4: THE ASSOCIATION BETWEEN BLOOD PRESSURE PER THE 2019 JSH AND 2017 ACC/AHA GUIDELINES AND HEART FAILURE RISK: THE SUITA STUDY. (January 2023) - Arafa, Ahmed; Kokubo, Yoshihiro; Teramoto, Masayuki; Kashima, Rena; Shimamoto, Keiko; Nakao, Yoko; Matsuo, Miki; Yoshihara, Fumiki; Izumi, Chisato
Abstract : Objective: Hypertension is a significant risk factor for heart failure (HF). Since hypertension definition varies across guidelines, identifying blood pressure (BP) categories that should be targeted to prevent HF is required. We, therefore, investigated the association between hypertension per the 2019 Japanese Society of Hypertension (JSH) and 2017 American College of Cardiology/American Heart Association (ACC/AHA) guidelines and HF risk. Design and method: A total of 2, 809 urban Japanese people registered in the Suita Study were followed up for incident HF, which was defined as participants with B-type natriuretic peptide levels of equal or higher than100 pg/mL or starting HF medications. Cox regression was used to assess HF risk for different BP categories in both guidelines compared to a reference category defined as systolic BP (SBP) less than120 mmHg and diastolic BP (DBP) less than 80 mmHg. Results: Within 8 years of median follow-up, 339 HF cases were detected. Per the 2019 JSH guidelines, elevated BP (SBP 130 to139 and/or DBP 80 to 89 mmHg), hypertension I (SBP 140 to159 and/or DBP 90 to 99 mmHg), hypertension II (160 to179 and/or DBP 100 to109 mmHg), hypertension III (SBP equal to or higher than180 and/or DBP equal to or higher than110 mmHg), and isolated systolic hypertension (SBP equal to or higher than 140 mmHg and DBP < 90 mmHg) were associated with increased HF risk with HRs (95% CIs): 1.82 (1.34 to 2.49), 1.57 (1.13 to 2.16), 2.10 (1.34 to 3.29), 2.57 (1.15 to 5.77), and 1.51 (1.04 to 2.19), respectively. Per the 2017 ACC/AHA guidelines, hypertension I (SBP 130 to 39 or DBP 80 to 89 mmHg), hypertension II (SBP equal to or higher than140 and/or DBP equal to or higher than 90 mmHg), and isolated systolic hypertension (SBP equal to or higher than 130 and DBP less than 80 mmHg) were associated with increased HF risk with HRs (95% CIs): 1.81 (1.33 to 2.47), 1.68 (1.24 to 2.27), and 1.64 (1.13 to 2.39), respectively. The associations were modestly attenuated among participants with no history of cardiovascular diseases (coronary heart disease or stroke). Hypertension medication dissolved the association between increased BP and HF risk. Conclusions: Increased BP, even without fulfilling the hypertension definition per the 2019 JSH guidelines, can elevate the risk of HF.